It's Ramadan, Curious George - Khan, Hena; Young, Mary O'Keefe (Boston : Houghton Mifflin Harcourt, 2016)
Curious George celebrates Ramadan with his friend Kareem by sampling special treats, making baskets to donate to the needy, and searching for the crescent moon.
Keywords: Board books; Ramadan -- Fiction; Monkeys -- Fiction; Stories in rhyme; Board books; Ramadan -- Fiction; Monkeys -- Fiction; Board books for children; Stories in rhyme